CONTEXTUAL TEACHING AND LEARNING (CTL) MODEL USING ‘REACH’ COMMUNICATION PATTERNS TO IMPROVE STUDENT LEARNING OUTCOMES - Yoyok Febrijanto; Erva Elli Kristanti (Suluh Adiluhung Publisher (SAPub), 2024)
This study used Contextual Teaching and Learning (CTL) model and Respect, Empathy, Audible, Clarity, and Humble (REACH) as a process for improving student learning outcomes in Study Program of Management of Health Information 1st grade. The objective was to improve student learning outcomes and found a model learning that suited students. Qualitative approach of initial observations with teacher interview, student learning outcomes at pre-cycle, exams at the end of the cycle, documentation, observation sheets, and field notes all contributed to the data collected for this classroom action research project. Data was reduced, presented, examined, and made conclusions. The results of this study analysis showed that in CTL process using REACH communication patterns showed positive results and were considered effective. The findings of this study indicated that the implementation of teaching and learning activities was in accordance with the learning model and could improve student learning outcomes in the cycle.